A case of foot drop treated with placenta pharmacopuncture - Woo-Seok Jang (Journal of Pharmacopuncture, 2009)
This study was to evaluate a case of foot drop treated with placenta pharmacopuncure. After thirteen times of treatment, I evaluated this case by the angle of dorsiflexion, the total sum of gaiting points, the time of heel standing. As a result of evaluation, the angle of dorsiflexion, total sum of gaiting points, time of heel standing were improved. The placenta pharmacopuncture can be used for foot drop and other peripheral nerve palsy.